Dimensions of subsets of cantor-type sets - Fang-Xiong Zhen (International Journal of Mathematics and Mathematical Sciences)
We define the Cantor-type set E first, and then the Besicovitch subset Bp of E. We mainly show the dimensions of subsets of Cantor-type set E in compatible case and incompatible case.